Where Trust Lies - Oke, Janette 1935-; Logan, Laurel Oke (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2015)
"After teaching in a 1920s mining town in western Canada, Beth Thatcher no longer feels at home among her wealthy family in the East, and her heart is torn between two very different worlds"--
Keywords: Women pioneers -- Fiction; Canada, Western -- Fiction; Christian fiction; Western stories; Love stories